Do nutritional habits and supplement use affect health-related quality of life during social isolation period in the community of North Cyprus? - Hoca, Mustafa; Elmas, Cemre; Kabaran, Seray (Taylor & Francis Ltd, 2024)
The aim of study was to comprehensively investigate the effect of nutritional habits and supplement use on health-related quality of life during social isolation period. This study was a cross-sectional study. A total of 418 participants (73.4% were women and 26.6% were men) participated in this study. Participants' demographic information, nutritional habits, and quality of life were questioned, and anthropometric measurements were obtained. A significant difference was found in the main meal skipping status of individuals by age group. The consumption of milk, yoghurt, ayran, legumes, cereal products other than bread, vegetables, fruits, oilseeds, and snack foods was similar in both periods. Furthermore, frequencies of multivitamins, multiminerals, vitamin B-12, vitamin C, vitamin D, iron, calcium, omega-3, and probiotics were similar during and before the pandemic. A significant difference was found in scores obtained on the Quality of Life Scale (QOLS) by age group. There was a significant difference in the quality of life scores by body mass index (BMI) groups. It was concluded that quality of life decreased due to the increase in body weight during pandemic period. The social isolation period did not make a clear difference in the nutritional habits of individuals and the use of nutritional supplements. When the main meal skipping situations were evaluated within the scope of nutritional habits, those who did not skip their main meal received the highest score on the QOLS.
Keywords: Coronavirus; nutrition; quality of life; supplement; pandemic